2003
DOI: 10.1099/ijs.0.02568-0
|View full text |Cite
|
Sign up to set email alerts
|

Alkanindiges illinoisensis gen. nov., sp. nov., an obligately hydrocarbonoclastic, aerobic squalane-degrading bacterium isolated from oilfield soils

Abstract: Alkanindiges illinoisensis gen. nov., sp. nov., an obligately hydrocarbonoclastic, aerobic squalanedegrading bacterium isolated from oilfield soils An alkane-degrading bacterium, designated GTI MVAB Hex1 T , was isolated from chronically crude oil-contaminated soil from an oilfield in southern Illinois. The isolate grew very weakly or not at all in minimal or rich media without hydrocarbons. Straight-chain aliphatic hydrocarbons, such as hexadecane and heptadecane, greatly stimulated growth; shorter-chain (¡C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…It has been reported that this type of methanotrophic bacteria was strongly associated with the oxic–anoxic interface in water columns or sediments, implying that oxic and anoxic zones were present in the SC soil. Another group (phylotypes BSC40 and BSC46) was related to Alkanindiges illinoisensis (91.3%), an aerobic squalane‐degrading bacterium recently isolated from oilfield soil (Bogan et al ., 2003). This bacterium has been reported to grow on long aliphatic hydrocarbons, including straight and branched ones, implying that organisms related to Alkanindiges may play a role in the aerobic degradation of petroleum hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that this type of methanotrophic bacteria was strongly associated with the oxic–anoxic interface in water columns or sediments, implying that oxic and anoxic zones were present in the SC soil. Another group (phylotypes BSC40 and BSC46) was related to Alkanindiges illinoisensis (91.3%), an aerobic squalane‐degrading bacterium recently isolated from oilfield soil (Bogan et al ., 2003). This bacterium has been reported to grow on long aliphatic hydrocarbons, including straight and branched ones, implying that organisms related to Alkanindiges may play a role in the aerobic degradation of petroleum hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, some oligotrophic bacteria (i.e. Their life strategy might be similar to that of the hydrocarbonoclastic bacteria (Bogan et al, 2003;Rojo, 2009), which have high environmental relevance in case of contamination. In contrast, many copiotrophs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Next the cells were washed with distilled water and stained with 1% aqueous uranyl acetate, then dehydrated in an ethanol series and embedded in Spurr resin. Thin sections were cut on an LKB Nova ultramicrotome, post-stained with uranyl acetate and lead citrate, and observed and photographed in a Zeiss EM-10CA TEM [43].…”
Section: Methodsmentioning
confidence: 99%